Evaluation of Mintrex® Copper as a Source of Copper in Broiler Diets - Wang, Zurong; Cerrate, Sandro; Coto, Cesar; Yan, Fenglan; Waldroup, P.W. (International Journal of Poultry Science, 2007)
This study was conducted to evaluate the bioavailability of an organic copper source, MINTREX® Cu, compared with reagent grade Cu sulfate as a source of Cu in broiler diets. Nutritionally complete basal diets were supplemented with either copper sulfate or MINTREX Cu to provide diets with 0, 10, 25, 50, 125, 250 and 500 mg kg-1 of supplemental Cu. Fifty commercial broiler strain (Cobb 500) male chicks were placed in each of 48 pens. Each diet (except for 500 mg kg-1) was fed to four replicate pens. The 500 mg kg-1 level was fed to two replicate pens for each source. There were two feeding phases including starter (0-21 d) and grower (21-35 d). At the end of each phase, birds were weighed by pens and two birds per pen (four birds per pen for the 500 mg kg-1 levels) were killed to take liver and tibia samples for analysis of Cu concentration. Overall, there was no effect of Cu source or dietary Cu concentration on feed conversion or mortality. At 14 d the birds in the MINTREX treatment weighed significantly more than the birds in the Cu sulfate treatment. High Cu concentrations markedly decreased (p